FOCAL MOTOR SEIZURES WITH TYPICAL AUTOMATISMS (FOCAL AUTOMOTOR SEIZURES) - M. B. Mironov; M. O. Abramov; K. Yu. Mukhin (Русский журнал детской неврологии)
The paper deals with the study of a group of patients with focal automotor seizures, by taking into consideration their nosological, anamnestic, clinical, electroencephalographic, and neuroimaging features.